Sex Hormone Levels and Pain Thresholds in the Luteal Phase of Healthy Women - Zhang L; Sun M; Ding W; Zhao N; Zhang W (International Journal of Women's Health, 2025)
Luyao Zhang,1 Mingyang Sun,1 Weiwei Ding,1 Nan Zhao,2 Wei Zhang1 1Department of Anesthesiology and Perioperative Medicine, Henan Provincial People’s Hospital, People’s Hospital of Zhengzhou University, Zhengzhou, People’s Republic of China; 2Department of Ultrasound, Henan Provincial People’s Hospital, People’s Hospital of Zhengzhou University, Zhengzhou, People’s Republic of ChinaCorrespondence: Wei Zhang, Department of Anesthesiology and Perioperative Medicine, Henan Provincial People’s Hospital, People’s Hospital of Zhengzhou University, No. 7 Weiwu Road, Zhengzhou, 450000, People’s Republic of China, Tel +86 037165580445, Email myhope2005@163.comObjective: To explore the relationship between the level of endogenous sex hormones in the luteal phase and the pain threshold of healthy subjects, and to find the influencing factors of the change in female pain threshold.Methods: Sixty-eight unmarried and nulliparous women, aged 22– 28 years old, had regular menstruation with a cycle of 26– 30 days, did not smoke, had no pain, no drug abuse, no gynecological problems, and had not participated in other clinical trials in the past 3 months. Blood was collected for analysis of sex hormone concentrations including follicle-stimulating hormone (FSH), luteinizing hormone (LH), and four different pain thresholds were measured after abdominal ultrasound confirmed that the menstrual cycle was in the luteal phase.Results: During the luteal phase, a greater cold pain threshold was correlated with lower FSH (β=− 0.743, P=0.012). A greater ischemic pain threshold was correlated with higher LH concentrations (β=1.397, P=0.011). A lower needle pain threshold was associated with higher FSH concentrations (β=0.32, P=0.006), which could explain 19.8% of the total variance of pain from a needle used to draw blood pain threshold.Conclusion: The needle pain threshold, cold pain threshold, ischemic pain threshold in the luteal phase of female healthy volunteers was, respectively, correlated with the concentrations of FSH or LH. These findings suggest that when formulating pain management strategies for women, the level of sex hormone concentrations should be considered, especially during the luteal phase, which may help provide more precise pain interventions for female patients and improve their pain experience.Keywords: follicle-stimulating hormone, luteinizing hormone, pain threshold, female healthy volunteers, luteal phase